Perlindungan Hukum Nasabah Bank Digital Syariah Di Indonesia Yang Berkepastian Hukum - Ariandi, Exy; Andika Wijaya; Rizki Setyobowo Sangalang (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
The Financial Services Authority (OJK) regulations in Indonesia, specifically POJK No. 12/POJK.03/2021 regarding Commercial Banks, serve as the legal basis for the operation of Digital Banks in Indonesia. This regulation, grounded in Law No. 10 of 1998 amending Law No. 7 of 1992 on Banking, allows Digital Banks to operate without physical branches, creating a legal vacuum, especially when compared to Islamic Banks. While the definition of Digital Banks is not explicitly mentioned in the regulation, the protection of Digital Bank customers remains a significant concern. POJK No. 12/POJK.03/2018 emphasizes that Digital Banks, including those based on Sharia principles, must comply with the provisions applicable to Indonesian Legal Entity Banks (BHI). Therefore, it is important to adopt specific regulations (Lex Specialis) governing Digital Islamic Banks to ensure better protection for customers. This research encourages the need for more specific regulations to protect the customers of Digital Banks, particularly Digital Islamic Banks, in creating a safer, more transparent digital banking environment that aligns with Sharia principles and protects the interests of customers in Indonesia